Roles & Responsibilities of National Land Agency in Efforts to Settle Land Ownership Disputes Due to Overlapping Certificates - Baqqi Zabidi Rois; Dahniarti Hasana; Denny Suwondo; Ira Alia Maerani (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to analyze: 1) The juridical implication is the existence of overlapping land certificates issued by the Cilacap Regency National Land Agency. 2) The roles and responsibilities of the Land Agency of Cilacap Regency in efforts to resolve land ownership disputes caused by overlapping land certificates. The approach method used in discussing this research problem is a sociological juridical approach. The specification of the research used descriptive analytical research. This type of data used primary and secondary data. The data analysis method used in this research is qualitative data analysis. The results of the study concluded: 1) The juridical implications of overlapping land certificates issued by the National Land Agency of Cilacap Regency and in one of the certificates being invalid. There are administrative legal defects that can result in the invalidity of a land title certificate. In addition, overlapping land certificates also creates legal uncertainty for land certificates. The existence of administrative legal defects in the issuance of the Certificate of Ownership has been canceled based on the Decision of the State Administrative Court Number: 28/G/2021/PTUN.SMG. 2). The roles and responsibilities of the Cilacap Regency Land Agency in Efforts to Settle Land Ownership Disputes resulting from Overlapping Land Certificates is to seek solutions to land dispute resolutions based on applicable laws and regulations by taking into account a sense of justice and respecting the rights and obligations of each party. The initial steps in dispute resolution that the BPN takes are deliberation / mediation. In addition to seeking settlement solutions, the Cilacap Regency BPN also plays a role in minimizing land disputes. The occurrence of overlapping land ownership as the cause of land disputes is absolutely the responsibility of the Head of the National Land Agency. So in the case of the overlapping certificate dispute in Cilacap Regency based on the decision Number: 28/G/2021/PTUN.SMG, BPN Cilacap must be responsible for implementing the court's decision by revoking the State Administrative Decision in the form of Property Rights Certificate (SHM) Number: 00898 / Karangpakis Village, BPN remains responsible for implementing the Administrative Court's decision on the cancellation of overlapping certificates, despite non-litigation efforts.